2006
DOI: 10.1007/s11270-006-9172-4
|View full text |Cite
|
Sign up to set email alerts
|

Dry and wet atmospheric deposition of nitrogen, phosphorus and silicon in an agricultural region

Abstract: We measured atmospheric nutrient deposition as wet deposition and dry deposition to dry and wet surfaces. Our analyses offer estimates of atmospheric transport of nitrogen (N), phosphorus (P) and silicon (Si) in an agricultural region. Annual dry and wet deposition (ha −1 year −1 ) was 0.3 kg of P, 7.7 kg of N, and 6.1 kg of Si; lower than or similar to values seen in other landscapes. N:P and Si:N imply that atmospheric deposition enhances P and Si limitation. Most P and soluble reactive P (SRP) deposition oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 33 publications
(86 reference statements)
11
95
1
1
Order By: Relevance
“…This decrease is mainly due to the drastic drop in sulphate content in wet deposits and that is in accordance to the research results obtained in different countries (Anderson, Downing 2006;Hertel et al 2003;Schöpp et al 2003;Kopácek et al 1997;EMEP 2004;Matzner 1989) as well as in other places of Lithuania (Jasinevičienė, Šopauskienė 1999;Šopauskienė, Būdvytytė 1994Šopauskienė, Būdvytytė , 1996. For example, sulphate contents in wet deposits decrease almost twice from 1994 to 1998 in the monitoring stations of NPs Aukštaitija, Žemaitija and Dzūkija, the later changes up to 2003 are not significant (Augustaitis et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…This decrease is mainly due to the drastic drop in sulphate content in wet deposits and that is in accordance to the research results obtained in different countries (Anderson, Downing 2006;Hertel et al 2003;Schöpp et al 2003;Kopácek et al 1997;EMEP 2004;Matzner 1989) as well as in other places of Lithuania (Jasinevičienė, Šopauskienė 1999;Šopauskienė, Būdvytytė 1994Šopauskienė, Būdvytytė , 1996. For example, sulphate contents in wet deposits decrease almost twice from 1994 to 1998 in the monitoring stations of NPs Aukštaitija, Žemaitija and Dzūkija, the later changes up to 2003 are not significant (Augustaitis et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…The general spring-summer increase at inland sites would reflect ammonia volatilisation from manure and fertilisers which are spread in the fields previous to maximum crop growth, usually in spring (Boixadera et al 2000). Similar spring maximum NH 4 + concentration related to agricultural activities has been reported elsewhere (Buishand et al 1988;Walker et al 2000;Anderson and Downing 2006). The coastal site of Begur presented the lowest farming activity, and correspondingly, its NH 4 + concentrations were the lowest and showed no significant seasonality (Table 2).…”
Section: Is Includedsupporting
confidence: 81%
“…Statistical analysis showed that dry deposition of nitrate and ammonium was higher than wet deposition throughout the year because of drier surface that attract more pollutants due to electrostatic charges (Anderson et al, 2006). The nitrate and ammonia major source of emission is vehicle, exhaust, coal combustion, fertilizer manufacturing, industrial process and burning of biomass (Li et al, 2013;Sutton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum wet deposition of ammonium and nitrate during high rainfall period obscured. Although lighter rain cleans the pollutants but heavy rainfall results in greater amount of deposit pollutants (Anderson et al, 2006). Significant increase of wet and dry deposition of nitrate was due to domestic heating, dry weather, low temperature and wind speed which led to more deposition of pollutants as these environmental condition does not allow the pollutants to transform into different compounds and diffuse (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%